Significant weak monsoon events during the early to middle Holocene transition: Pollen evidence from an alpine lake in North China. (15th April 2022) - Zhang, Shengrui; Wang, Dandan; Li, Manyue; Yan, Fangqing; Xu, Qinghai
Abstract: The response characteristics of East Asian summer monsoon (EASM) precipitation to abrupt climatic events during the early to middle Holocene transition may provide insights into the response of EASM precipitation to possible extreme climatic events under future global warming scenarios. We present a high-resolution (∼10 yr) pollen record from a hydrologically closed alpine lake (Yazihai Lake) in North China spanning the interval of 9000–7500 cal yr BP. The results reveal two significant weak monsoon events during 8830–8730 cal yr BP and 8100–8000 cal yr BP. Based on a comparison with the GRIP δ 18 O ice core record from Greenland and the stalagmite δ 18 O record from Dongge Cave in South China, we suggest that the second weak monsoon event (8100–8000 cal yr BP) recorded at Yazihai Lake corresponds to the 8.2 ka event that originated in the North Atlantic region, it is spatially and temporally synchronous between the northern and the southern parts of the EASM region and is characterized by a significant decrease in EASM precipitation. For the first weak monsoon event (8830–8730 cal yr BP) recorded at Yazihai Lake, it was also captured by pollen, stalagmite δ 18 O, and marine sedimentary records from middle to low latitudes of the Northern Hemisphere, and its nature and amplitude resemble the 8.2 ka event. We infer that the possible cause of these two significant weak monsoon events was related to the southward shift of the intertropical convergence zone (ITCZ) due to the collapse of the Atlantic Meridional Overturning Circulation (AMOC), triggered by meltwater influx to the North Atlantic Ocean, and that the abrupt climate signals were transmitted via the monsoon circulation from low latitudes to middle–high latitudes in the EASM region. Highlights: Two significant weak monsoon events occurred in North China during 9000–7500 cal yr BP. Details are given on the effects and structure of the 8.2 ka event in North China. Possible causes of two significant weak monsoon events are discussed.